Peptidoglycan O-Acetylation as a Virulence Factor: Its Effect on Lysozyme in the Innate Immune System - Ashley S. Brott; Anthony J. Clarke (MDPI AG, 2019)
The peptidoglycan sacculus of both Gram-positive and Gram-negative bacteria acts as a protective mesh and provides structural support around the entirety of the cell. The integrity of this structure is of utmost importance for cell viability and so naturally is the first target for attack by the host immune system during bacterial infection. Lysozyme, a muramidase and the first line of defense of the innate immune system, targets the peptidoglycan sacculus hydrolyzing the β-(1→4) linkage between repeating glycan units, causing lysis and the death of the invading bacterium. The O-acetylation of N-acetylmuramoyl residues within peptidoglycan precludes the productive binding of lysozyme, and in doing so renders it inactive. This modification has been shown to be an important virulence factor in pathogens such as Staphylococcus aureus and Neisseria gonorrhoeae and is currently being investigated as a novel target for anti-virulence therapies. This article reviews interactions made between peptidoglycan and the host immune system, specifically with respect to lysozyme, and how the O-acetylation of the peptidoglycan interrupts these interactions, leading to increased pathogenicity.